Genetic analysis with pyrosequencing using loop pipetting and a light dependent resistor. Issue 42 (14th October 2021) - Iqbal, Faisal; Shabbir, Muhammad Imran
Abstract : A DNA sequencer called LoopSeeq was developed using pyrosequencing chemistry where iterative addition of dNTPs was performed by contact dispensing through a loop pipette and detection of chemiluminescence with inexpensive light sensor LDR for point-of-care applications. Abstract : DNA sequencing is among the most important techniques in biology to decipher the key genetic players of health and disease. The existing laboratory instruments for DNA sequencing are well established and reliable. However, these instruments are still out of reach of most laboratories in the world due to very high equipment and running costs and require trained personnel to keep them running. These instruments are also large and bulky making them unsuitable for analysis in remote settings away from laboratories. Here we describe a proof-of-concept of a DNA sequencing device LoopSeeq using a simple approach to address the said problems without minimizing the quality of results. The device was designed to perform pyrosequencing by iterative addition of dNTPs by contact dispensing through a loop pipette (loopette) and detection of chemiluminiscence with the cheapest sensor in the market, a light dependent resistor (LDR). Two small geared motors drive the moving parts in a controlled and coordinated manner with the help of a motor driver circuit, an Arduino Nano microcontroller and two small neodymium magnets. The real-time light intensity data from the LDR were transferred to a laptop computer for further analysis. Pyrosequencing was optimized using 55 nt self-primed oligo. In order to demonstrate the DNA sequencing ability with real samples, molecular genetic analysis was performed for a previously identified novel mutation from our lab in exon4 of the OCA2 gene. LoopSeeq successfully identified the homozygous normal (c.408-409_AA), homozygous mutant (c.408-409_delAA) and heterozygous carrier (c.408-409_AA/delAA) alleles in three individuals of a family affected with oculocutaneous albinism (OCA). Further, this can be implemented for molecular diagnostic applications for bacterial, viral or other pathogen detection and genotyping among different subtypes following some reports described earlier. A few drawbacks in the current implementation including the evaporation of liquid reagents, possible loopette contamination, etc. associated with use for longer times are also described along with suggestions to rectify these problems in future designs. With the described capabilities, the LoopSeeq device can be implemented in routine labs as well as in several real-world situations where conventional DNA sequencing instruments are unfeasible, for example, diagnostic testing at remote settings or at the point-of-care.